Apprenticing Teachers Reading: The Cultural Significance of Juvenile Melodrama - Radford, Linda Anne (Journal of the Canadian Association for Curriculum Studies, 2009)
This article presents a study that reveals the educational significance of melodrama as a moral aesthetic, specifically in relation to work with literacies around identity in the teacher education classroom. Using methods of Lacanian discourse analysis and genre analysis, it unmasks the way two-award winning juvenile historical fictions depend on melodrama to instigate their narrative appeal. It unravels the skein of melodrama’s particularity and complicated affective potential for teachers who want to work in liberating ways with youth fiction in the classroom.